Chemical Potential Switching of the Anomalous Hall Effect in an Ultrathin Noncollinear Antiferromagnetic Metal. Issue 24 (16th May 2022) - Qin, Peixin; Yan, Han; Fan, Benshu; Feng, Zexin; Zhou, Xiaorong; Wang, Xiaoning; Chen, Hongyu; Meng, Ziang; Duan, Wenhui; Tang, Peizhe; Liu, Zhiqi
Abstract: The discovery of the anomalous Hall effect in noncollinear antiferromagnetic metals represents one of the most important breakthroughs for the emergent antiferromagnetic spintronics. The tuning of chemical potential has been an important theoretical approach to varying the anomalous Hall conductivity, but the direct experimental demonstration has been challenging owing to the large carrier density of metals. In this work, an ultrathin noncollinear antiferromagnetic Mn3 Ge film is fabricated and its carrier density is modulated by ionic liquid gating. Via a small voltage of ≈3 V, its carrier density is altered by ≈90% and, accordingly, the anomalous Hall effect is completely switched off. This work thus creates an attractive new way to steering the anomalous Hall effect in noncollinear antiferromagnets. Abstract : Noncollinear antiferromagnetic metals are hot spots in the magnetic community. The chemical potential is found to effectively switch on/off the anomalous Hall effect (AHE) of such metals, which opens a new path to tuning the AHE and experimentally validates the essential role of chemical potential in theoretical calculations for determining the anomalous Hall conductivity.